2013
DOI: 10.1111/fwb.12295
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for iron‐regulated cyanobacterial predominance in oligotrophic lakes

Abstract: 1. Cyanobacterial harmful algal blooms (cyanoHABs) are most often associated with large eutrophic lakes. In the past decade, an increase in the incidence of cyanoHABs in small oligotrophic lakes within the Laurentian Great Lakes-St. Lawrence River Basin has been documented. We explored macro-and micronutrient conditions during peak phytoplankton biomass that result in high cyanobacterial densities. 2. We hypothesised that the availability of biologically available iron (Fe) both limits the assimilation of phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…This strategy locks Fe 3+ into siderophore-bound complexes that are unavailable to other algae that do not have a siderophore-Fe uptake system and may act to limit their population growth. Indeed, Sorichetti, Creed and Trick (2014a) found that siderophores lower 'free' (modelled) Fe 3+ to extremely low concentrations. Siderophores do not appear to be responsible for initiating blooms but could be essential in maintaining them by limiting eukaryotic access to Fe (Murphy, Lean & Nalewajko, 1976).…”
Section: Acquiring Fe With Siderophoresmentioning
confidence: 99%
“…This strategy locks Fe 3+ into siderophore-bound complexes that are unavailable to other algae that do not have a siderophore-Fe uptake system and may act to limit their population growth. Indeed, Sorichetti, Creed and Trick (2014a) found that siderophores lower 'free' (modelled) Fe 3+ to extremely low concentrations. Siderophores do not appear to be responsible for initiating blooms but could be essential in maintaining them by limiting eukaryotic access to Fe (Murphy, Lean & Nalewajko, 1976).…”
Section: Acquiring Fe With Siderophoresmentioning
confidence: 99%
“…This may be due to the tendency for Fe to bind to DOM in oxic surface waters, which results in Fe-DOM complexes that render Fe nonbioavailable for cellular use while bound (Fujii et al, 2014). Sorichetti et al (2014a) and I.F. Creed (unpubl.…”
Section: Water Chemistry Total Algal and Cyanobacterial Biomassmentioning
confidence: 99%
“…However, few field studies have been conducted in freshwater environments (e.g. Murphy et al ., ; Sorichetti et al ., ,b), and to the best of our knowledge, none compares the role of Fe in regulating cyanobacterial biomass across a lake trophic gradient. This study built upon the limited findings available from oligotrophic freshwater environments to explore the relationship between Fe supply and bioavailability to cyanobacterial biomass and Fe‐binding ligand concentrations in temperate lakes that span a range of trophic states from ultra oligotrophic to hypereutrophic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among our set of lakes, cyanobacterial density was highest when TDFe concentration was low. This is consistent with laboratory (Kerry et al ., ) and lake (Sorichetti et al ., ) research showing that cyanobacteria are competitive over eukaryotes at low Fe concentrations. Previous research has attributed this competitive advantage to the ability of cyanobacteria when Fe‐limited to use Fe‐binding ligands, hydroxamate and catecholate siderophores.…”
Section: Discussionmentioning
confidence: 99%